Role of Pel and Psl polysaccharides in the response of Pseudomonas aeruginosa to environmental challenges: Oxidative stress agents (UVA, H2 O2, sodium hypochlorite) and its competitor Staphylococcus aureus - Grossich, Romina (2023)
Pseudomonas aeruginosa is a versatile bacterium capable of adapting to a wide range of stress factors, including solar UVA radiation (400–315 nm). High UVA doses produce lethal effects due to the action of reactive oxygen species. Sublethal UVA doses also induces oxidative damage, but, in addition, it triggers a variety of adaptive responses, including the over-expression of pelA and pslA genes in P. aeruginosa. These genes encode the synthesis of Pel and Psl, which are essential polysaccharides in biofilm formation. The present study analysed the role of Pel and Psl in the adaptive responses gener-ated by exposure to low UVA doses, and their importance in the response to lethal doses of UVA, hydrogen peroxide (H2 O2), and sodium hypochlorite, in both planktonic cells and submerged and air–liquid interface (ALI) biofilms. It also studied the roles of Pel and Psl in P. aeruginosa–Staphylococcus aureus interaction. The results demonstrate that the capacity of sub-lethal UVA exposure to increase cell hydrophobicity and cell attachment and generate cross-protection phenomena in P. aeruginosa depends on the presence of Pel and Psl. The study also shows that Pel and Psl have a key role in the tolerance to lethal doses of UVA radiation, sodium hypochlorite and H2 O2, in both biofilms and planktonic cells. Finally, co-culture assays showed total inhibition of S. aureus growth in presence of P. aeruginosa. This phenomenon depends, at least in part, on the simultaneous presence of Pel and Psl in planktonic cells and biofilms, suggesting a relevant role of these polysaccharides in the interaction between these species.